UJI PUPUK KANDANG KAMBING DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL CABE RAWIT (Capsicum frutescens L. ) UMUR 100 HARI: Pupuk NPK, Cabe Rawit, Pupuk Kandang - Lintang Abyudaya, Taru; Siswadi, Siswadi; Santosa, Sartono Joko (innofarm, 2024)
Test of goat manure and NPK fertilizer on the growth and yield of cayenne pepper (Capsicum frutescens l.) 100 days old. Implementation of this research was carried out in their own garden. In February 2023 – April 2023. The aim is to find out and analyze the effect of differences in planting media and doses of goat drum fertilizer and NPK fertilizer on the growth and yield of cayenne pepper plants. The experimental design used in this research was a Completely Randomized Design (CRD) which consisted of two factors, namely Goat Manure and NPK. Three (3) replications will be applied to each experiment consisting of: Goat Manure Dosing Factor (K) consisting of four (4) levels, namely; K0 = Goat manure dose 0 tons/ha or 0 g/plant, K1 = Goat manure dose 5 tons/ha or 80 g/plant, K2 = Goat manure dose 10 tons/ha or 160 g/plant, K3 = The dose of goat manure is 15 tonnes/ha or 240 g/plant. The second factor is administering the NPK (N) dose which consists of four (4) levels, namely; N0 = NPK fertilizer dose 0 kg/ha or 0 g/plant, N1 = NPK fertilizer dose 150 kg/ha or 2.5 g/plant, N2 = NPK fertilizer dose 300 kg/ha or 5 g/plant, N3 = Dosage NPK fertilizer 450 kg/ha or 7.5 g/plant. To determine the effect of the treatment dose above, the F test was used through analysis of variance (ANOVA). Meanwhile, to determine the significance of the treatment, the Honestly Significant Difference Test (BNJ) was used at a level of 5%. Observation parameters are plant height, flower appearance, number of flowers, number of fruit, fruit weight, fruit length, fruit diameter, number of remaining fruit. Goat manure has no effect on the parameters of plant height, flower appearance, number of flowers, number of fruit, fruit weight, fruit length, fruit diameter except for the parameter of the number of remaining fruit. NPK fertilizer has an effect on the parameters of fruit diameter, but has no effect on the parameters of plant height, flower appearance, number of flowers, number of fruit, fruit weight, fruit length. The interaction between goat manure (K) and NPK fertilizer (N) did not have a significant effect on the parameters. Keywords: NPK Fertilizer, Cayenne Pepper, Manure